PENGARUH GAYA HIDUP DAN HARGA TERHADAP KEPUTUSAN BERKUNJUNG BACKPACKER INDONESIA KE YOGYAKARTA - Apriani Riati; Nanny Roedjinandari; Andini Risfandini (Universitas Merdeka Malang, 2020)
Backpacking has become part of lifestyle and has been developed since the year of 1990. The visit intention of member of the backpacker community in Indonesia to go to Yogyakarta is influenced by lifestyle and price. This research aims: (1) to investigate the influence of lifestyle to visit intention of Indonesian backpacker to Yogyakarta; (2) to investigate the influence of price to visit intention of Indonesian backpacker to Yogyakarta; (3) to investigate the influence of price and lifestyle simultaneously to visit intention of Indonesian backpacker to Yogyakarta; (4) to investigate which one between lifestyle and price that dominantly influence visit intention of Indonesian backpacker to Yogyakarta. Quantitative research with descriptive statistic analysis and multiple regression analysis is used to test whether intention to visit is influenced by lifestyle and price. This research is using 100 respondent as the sample of the research. Based from data that is collected using online questionnaire, it is concluded that lifestyle and price influence intention to visit partially and simultaneously. Price has a more dominant influence to visit intention of Indonesian backpacker to Yogyakarta.